Crystal structure of pyruvate decarboxylase from Zymobacter palmae. Issue 9 (8th September 2016) - Buddrus, Lisa; Andrews, Emma S. V.; Leak, David J.; Danson, Michael J.; Arcus, Vickery L.; Crennell, Susan J.
Abstract : The crystal structure of Z. palmae pyruvate decarboxylase was elucidated at 2.15 Å resolution. Abstract : Pyruvate decarboxylase (PDC; EC 4.1.1.1) is a thiamine pyrophosphate‐ and Mg 2+ ion‐dependent enzyme that catalyses the non‐oxidative decarboxylation of pyruvate to acetaldehyde and carbon dioxide. It is rare in bacteria, but is a key enzyme in homofermentative metabolism, where ethanol is the major product. Here, the previously unreported crystal structure of the bacterial pyruvate decarboxylase from Zymobacter palmae is presented. The crystals were shown to diffract to 2.15 Å resolution. They belonged to space group P 21, with unit‐cell parameters a = 204.56, b = 177.39, c = 244.55 Å and R r.i.m. = 0.175 (0.714 in the highest resolution bin). The structure was solved by molecular replacement using PDB entry2vbi as a model and the final R values were R work = 0.186 (0.271 in the highest resolution bin) and R free = 0.220 (0.300 in the highest resolution bin). Each of the six tetramers is a dimer of dimers, with each monomer sharing its thiamine pyrophosphate across the dimer interface, and some contain ethylene glycol mimicking the substrate pyruvate in the active site. Comparison with other bacterial PDCs shows a correlation of higher thermostability with greater tetramer interface area and number of interactions.